To Assess the Relationship Between Reticulocyte Hemoglobin Content and Iron Status in Hemodialysis-Dependent Patients - Hassan, Sameen; Lateef, Attia; Shahid , Rafiq Ahmad; Aziz Gillani, Mona (Journal of University College of Medicine and Dentistry, 2024)
Objectives: This study aims to evaluate the diagnostic utility of reticulocyte hemoglobin content (RET-He) and its correlation with transferrin saturation (TSAT) and other iron markers for identifying iron deficiency anemia in hemodialysis patients. Methods: The study was conducted at Hematology Department of Shaikh Zayed Hospital in Lahore, from March 2022- April 2023. Total 120 patients with chronic kidney disease on hemodialysis were enrolled in this study. Ferritin was determined by chemiluminescence immunoassay. Flow cytometry and spectrophotometry was performed to determine RET-He and iron status including serum iron and Total iron binding capacity (TIBC). Patients of both genders, aged 18-80 and those on hemodialysis for 3 months or more were selected. Patients excluded were those with bleeding from any site in last three months, received oral or parenteral iron supplementation in one month. Results: In this study, 120 hemodialysis dependent chronic kidney disease patients were enrolled. Among them, 65 (54.2%) were males, while 55 (45.8%) were females; 18 years to 80 years was the age range, with 53.48 ± 13.782 years being mean age. Mean RET-He was 29.439 ± 3.51 pg/cell, while mean serum iron was 68.96 ± 38.63 µg/dl, mean TIBC was 224.41 ± 55.109 µg/dl, serum ferritin mean value being 386.91 ± 357.51 ng/ml and mean TSAT was 31.93 ± 18.52%. Sensitivity (Se) was 56.0%, specificity (Sp) was 74.6%, positive predictive value (PPV) 36.8%, negative predictive value (NPV) 86.6% and accuracy of RET-He in diagnosing Iron deficiency anemia was 70.8% respectively. Conclusion: Reticulocyte hemoglobin content is highly effective in diagnosing iron deficiency anemia in chronic kidney disease patients. Its lower cost compared to traditional markers makes it a valuable tool for clinical practice.